Epidemiology and clinical manifestations of reported Lyme disease cases: Data from the Canadian Lyme disease enhanced surveillance system. - Kiera Murison; Christy H Wilson; Katie M Clow; Salima Gasmi; Todd F Hatchette; Annie-Claude Bourgeois; Gerald A Evans; Jules K Koffi (PLoS ONE)
Lyme disease cases reported in seven Canadian provinces from 2009 to 2019 through the Lyme Disease Enhanced Surveillance System are described herein by demographic, geography, time and season. The proportion of males was greater than females. Bimodal peaks in incidence were observed in children and older adults (≥60 years of age) for all clinical signs except cardiac manifestations, which were more evenly distributed across age groups. Proportions of disease stages varied between provinces: Atlantic provinces reported mainly early Lyme disease, while Ontario reported equal proportions of early and late-stage Lyme disease. Early Lyme disease cases were mainly reported between May through November, whereas late Lyme disease were reported in December through April. Increased awareness over time may have contributed to a decrease in the proportion of cases reporting late disseminated Lyme disease. These analyses help better describe clinical features of reported Lyme disease cases in Canada.